Characterization and Deconstruction of Oligosaccharides in Black Liquor From Deacetylation Process of Corn Stover - Wang, Wei; Chen, Xiaowen; Katahira, Rui; Tucker, Melvin (Frontiers in Energy Research, 2019)
The National Renewable Energy Laboratory (NREL) developed low severity Deacetylation and Mechanical Refining (DMR) process under atmospheric pressure, generates highly fermentable, low toxicity sugar syrups and highly reactive lignin streams. The dilute alkali deacetylation step saponifies acetyl groups from the hemicellulosic fraction of biomass into a black liquor waste stream that also contains solubilized acetic, ferulic, p-coumaric acids, lignin-carbohydrate complexes (LCCs), oligosaccharides, and solubilized lignin. Valorization of the soluble components in the deacetylation black liquor waste stream requires characterization of the black liquor. Our analyses show that glucan, xylan, and lignin were three main components in black liquor and the oligosaccharides in the black liquor were mainly dimers and trimers with arabinofuranose branch groups mainly on the xylooligomers. GPC chromatograms showed that the black liquor also contained oligomeric lignin moieties with molecular weights ranging between 1,800 and ~10,000 Da. Enzymatic saccharification of the black liquor was conducted based on the compositional and structural information. Incorporation of commercial cellulase and hemicellulase enzyme preparations with various accessary enzymes showed up to 57% hydrolysis of the xylooligosaccharides in the black liquor to monomeric sugars, which could be used to improve biorefinery carbon utilization in biological fermentations to improve end product fuel or bioproduct volumes per metric ton of biomass processed. This is so far the first study about characterizing DMR black liquor and exploring breaking down the oligosaccharides in black liquor for potential use.